As transformações geométricas em um jogo interativo entre quadros: um estudo teórico - Lino, Eliedete Pinheiro (2014)
This research deals with the geometric transformations in order to present a broader view of this content, a vision of geometry with a new organization of these changes and give more meaning to their study. Due to this objective we used as a theoretical framework for the research, the notion of context evidenced by Douady as consisted by objects in a field of mathematics and its possible relationships and also the context of the change of the idea that a subject can mobilize in the search of the solution of a problem. For the author to translate a problem from a frame to another is specifically intended to enable the deployment of other tools, other than those initially used for solving a problem. We also used the concept of Rogalski´s point of view because it allows us to approach a problem from different points of view within the same framework. Thus, we focused our analysis on views that can be mobilized within the geometry framework in the context of analytic geometry and algebra framework, that is, from the choice of a mathematics framework in which it is studied the geometric transformations we seek to identify the various possible points of view. We still appealed to Duval´s Semiotics Representation Registers which are used to represent geometric transformations and also to the possible transformations of these records as from the treatment and conversion. To the author the knowledge about a mathematical object can be seized from at least two records and that the conversion of records allows to develop the coordination of these various records. These actions will allow the students the understanding of the discovery and the development of the knowledge. The methodology used was based on scientific literature domain documents such as books, articles, dissertations and theses that addressed our object of study. This methodological choice contributed to the achievement of our goal since it allowed us to "look" geometric transformations and present them in a study from the early series with folding to the higher education addressing them in the context of Algebra, Analytical Geometry and Geometry frameworks